Internet addiction (Facebook as a model) and its relationship to family disintegration among Tikrit University students - Zakaria Abdel Ahmed (مجلة جامعة الأنبار للعلوم الإنسانية, 2021)
Research summary: The current research aims to:1- Knowing the level of addiction to Facebook among university students2- Identify the differences in addiction to Facebook according to the specialty variable (scientific) (human)3- Knowing the level of family disintegration among university students4- Knowing the correlation between Facebook addiction and family disintegration among university students.For the purpose of achieving the above goals, the researcher built the two measures of addiction to Facebook, family disintegration, by following the necessary scientific procedures. The researcher chose a random stratified sample of university students, which is the (second) and (third) grade, and the researcher used the appropriate statistical means to build the two scales and extract the results from them. . The T-value, QA square, percentage, T-test for one sample, T-test for two independent samples, Pearson correlation coefficient, and the following results were shown: